Epithelial Infection With Candida albicans Elicits a Multi-System Response in Planarians - Maciel, Eli Isael; Valle Arevalo, Ashley; Ziman, Benjamin; Nobile, Clarissa J.; Oviedo, Néstor J. (Frontiers in Microbiology, 2021)
Candida albicans is one of the most common fungal pathogens of humans. Prior work introduced the planarian Schmidtea mediterranea as a new model system to study the host response to fungal infection at the organismal level. In the current study, we analyzed host-pathogen changes that occurred in situ during early infection with C. albicans. We found that the transcription factor Bcr1 and its downstream adhesin Als3 are required for C. albicans to adhere to and colonize the planarian epithelial surface, and that adherence of C. albicans triggers a multi-system host response that is mediated by the Dectin signaling pathway. This infection response is characterized by two peaks of stem cell divisions and transcriptional changes in differentiated tissues including the nervous and the excretory systems. This response bears some resemblance to a wound-like response to physical injury; however, it takes place without visible tissue damage and it engages a distinct set of progenitor cells. Overall, we identified two C. albicans proteins that mediate epithelial infection of planarians and a comprehensive host response facilitated by diverse tissues to effectively clear the infection.